Comparison of a smartphone-based ECG recording system with a standard cardiac event monitor in the investigation of palpitations in children. Issue 1 (2nd June 2018) - Macinnes, Mairi; Martin, Nicholas; Fulton, Helen; McLeod, Karen A
Abstract : Background: The AliveCor (Kardia) monitor attaches to a smartphone and allows a single-lead ECG to be recorded during symptoms. In 2016, we introduced the use of this smartphone device for investigating palpitations, without syncope, in children. The aim of our study was to review our experience with the smartphone device, comparing it with our previous standard conventional approach to cardiac event monitoring using the Cardiocall monitor, which uses skin electrodes and is given for a finite period. Methods: Over a period of 24 months, 80 smartphone monitors were issued and compared with the most recent 100 conventional event monitors. The number of ECG recordings received, arrhythmias documented, quality of ECG recordings and patient satisfaction were evaluated. Results: Median patient age was 11 years in the smartphone monitor group compared with 10 years in the conventional group. Seventy-nine of 80 (98%) patients with a smartphone monitor sent an ECG recorded during symptoms, compared with 62/100 (62%) from the conventional group. A total of 836 ECG recordings were sent from the smartphone monitors compared with 752 from the conventional group. Eight per cent of ECG recordings in each group were of inadequate quality for analysis. Twenty of 80 (25%) patients with a smartphone monitor had documented tachyarrhythmia compared with 6/100 (6%) patients with the conventional monitor (p<0.001). On comparison with the conventional approach, the smartphone monitor outperformed with respect to diagnostic yield and patient satisfaction. Conclusions: A smartphone-based event monitor allows simple, effective, long-term ECG event monitoring in children that is highly acceptable to the patient and parent.